The political role of black journalists in Post-apartheid South Africa : the case of the City Press – 1994 to 2004 - Sesanti, Simphiwe Olicius (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD )--University of Stellenbosch, 2011.